Parent Care Patterns in Improving Social Intelligence in Basic School Children in SOS Children’s Village Semarang - Imarah, Hana Nisrina; Arbarini, Mintarsih (Universitas Negeri Semarang, 2024)
This study aims to describe the form of foster care patterns implemented in SOS Children's Village Semarang and the parenting patterns of parents in the social intelligence of elementary school children in SOS Children's Village. This research uses a qualitative approach with qualitative descriptive methods. The subjects in this study were 1 supervisor, 3 foster mothers, and 3 children. The data collection technique is done using interviews, observation, and documentation. The results of this study showed that the parenting styles applied by foster children at SOS Children's Village Semarang use parenting styles that tend to be democratic. The way of parenting applied at SOS Children's Village Semarang has been named Family Base Case, which is family-based care. This concept of parenting involves the foster mother as the main center in parenting, the child as a brother or sister. Then, the children's social intelligence at SOS Children's Village Semarang is sufficient to fulfill all aspects of their social skills. Such as communication skills, humor-making skills, friendship skills, group role skills, and politeness skills.